ISSUES OF IMPLEMENTING LARGE-SCALE SPECIAL TOPOGRAPHIC SURVEYS - A.I. Karshiboev; A.A. Khakimov; J.Sh. Khikmatilloev (PEDAGOGS, 2024)
Abstract. Large-scale special topographic surveys that are widely used to solve various engineering tasks in construction, design and other industries. Special attention is paid to the need to ensure high accuracy when creating topographic plans and maps. The main stages of surveying are described, including collection and processing of materials, creation of geodetic networks and plan maps, as well as methods of process automation and use of modern geodetic tools. Also important in the study are the requirements for survey accuracy and the plans created on their basis, with an indication of standards and allowable deviations.